2016
DOI: 10.1242/jcs.182469
|View full text |Cite
|
Sign up to set email alerts
|

Role of cytonemes in Wnt transport

Abstract: Wnt signaling regulates a broad variety of processes during embryonic development and disease. A hallmark of the Wnt signaling pathway is the formation of concentration gradients by Wnt proteins across responsive tissues, which determines cell fate in invertebrates and vertebrates. To fulfill its paracrine function, trafficking of the Wnt morphogen from an origin cell to a recipient cell must be tightly regulated. A variety of models have been proposed to explain the extracellular transport of these lipid-modi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
90
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(91 citation statements)
references
References 88 publications
1
90
0
Order By: Relevance
“…Cell clustering through horizontal processes may be a general feature of butterfly wing epithelium, which would contribute to cellular communication. In Drosophila , cytonemes play a critical role in distributing morphogenic signal proteins3536373839. It is possible that the horizontal processes that were observed in this study function as cytonemes to distribute morphogenic signal proteins.…”
Section: Discussionmentioning
confidence: 80%
“…Cell clustering through horizontal processes may be a general feature of butterfly wing epithelium, which would contribute to cellular communication. In Drosophila , cytonemes play a critical role in distributing morphogenic signal proteins3536373839. It is possible that the horizontal processes that were observed in this study function as cytonemes to distribute morphogenic signal proteins.…”
Section: Discussionmentioning
confidence: 80%
“…One possibility is that WNT and HH may not need to diffuse in order to act at a long range. Indeed, it has been suggested that these proteins could remain tethered to specialised signalling filopodia called cytonemes, which extend to distant cells (Bischoff et al, 2013;Hsiung et al, 2005;Ramirez-Weber and Kornberg, 1999;Stanganello and Scholpp, 2016). However, there is as yet no specific means of preventing cytoneme formation, precluding a direct test of this model.…”
Section: The Role Of Exosomes In Developmental Signallingmentioning
confidence: 99%
“…Wnts bind to cell surface receptors to activate diverse signaling pathways, the beststudied of which leads to the stabilization of β -catenin and the activation of target gene expression. Less is known about how Wnts travel from one cell to engage receptors on neighboring cells (Yamamoto et al 2013;Yu & Virshup 2014;Stanganello & Scholpp 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Several contrasting models have been proposed to explain how Wnts travel from the producing cell to the receiving cell (reviewed in Stanganello & Scholpp 2016). All models 50 must explain how the hydrophobic palmitoleate moiety on Wnt is protected from an aqueous environment.…”
Section: Introductionmentioning
confidence: 99%